Hubungan Unsafe Action Dengan Kejadian Kecelakaan Kerja Pada Pekerja Devisi Workshop Di PT. X - Yuyun Riantika; Nuryani, Dina Dwi; Samino, Samino; Muhani, Nova (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
ABSTRACT Throughout 2020, there were 35,291 cases recorded (with a proportion of 42.2%). The majority of accidents occur due to human error which causes material and moral losses for both companies and workers. The aim of the research is to determine the relationship between unsafe action and work accidents among workshop division workers at PT. X. This research is a quantitative research with a cross sectional design with a sample size and population of 50 workers using a total sampling technique. used was Pusposive Sampling using univariate and bivariate analysis tests. To determine the frequency distribution of the independent variable and determine the relationship between the independent variable (unsafe action) and the dependent variable (work accident) use the Chi Square Test. The research results showed that 18 workers (36.0%) had experienced work accidents and 32 workers (64.0%) had never experienced work accidents. There were 22 workers who had experienced unsafe action (44.0%) and 28 workers who had never experienced unsafe action (56.0%). The results of the chi-square test show a value (p-value 0.034) so it can be concluded that there is a significant relationship between safe action and the incidence of work accidents among workshop division workers at PT. X with OR 3.951. Workers are expected to use complete PPE and always obey the regulations. It is hoped that the company can provide socialization and safety training regarding unsafe actions and work accidents to all workers, increase supervision and discipline, and improve the K3 culture in the work environment. Keywords: Unsafe Action; Work Accident; Workshop